Privacy and Emotional Intelligence in Technology-Based Learning - Frolova, Yuliya (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2025)
This study explores the influence of emotional intelligence and privacy orientation on attitudes and intentions to learn with mobile technologies. Data were collected from 272 respondents in Kazakhstan, a country with a transitioning economy. The findings reveal that both emotional intelligence and privacy orientation positively affect attitudes and intentions, except for the dimension of concern about one’s own informational privacy. Additionally, a model incorporating both emotional intelligence and privacy orientation explains variations in attitudes and intentions more effectively than models with either factor alone. This research contributes to the understanding of the multidimensional constructs of mobile learning, privacy, and emotional intelligence in non-Western contexts, providing valuable insights for technology adoption in transitional economies.